Cash optimization with cash management model approach: The case of PT Pertamina Gas (Pertagas) - William Ben Gunawan (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2025)
This study examines the optimization of corporate cash management at Pertagas amid heightened volatility in the energy sector, fluctuating exchange rates, inflationary pressures, and internal demands for CapEx–OpEx efficiency. Using a quantitative approach, this research evaluates Pertagas’s cash cycle and liquidity profile, and applies five cash management models—Baumol, Beranek, Miller-Orr, Stone, and Orgler—to determine optimal cash balances under varying assumptions of certainty and uncertainty. Results indicate substantial volatility in net cash flows, with a Value at Risk (VaR) of –USD 81.48 million at the 95% confidence level. Model estimations recommend optimal daily cash levels ranging from USD 1.05 million (Baumol) to USD 4.51 million (Miller-Orr), significantly lower than the company’s existing Rp 200 billion (≈ USD 12.5 million) policy threshold, implying notable opportunity costs from holding idle cash. The Orgler model further shows that Pertagas could generate up to USD 10.89 million annually through optimized deployment of surplus liquidity. The study recommends integrating stochastic and forecasting-based models, strengthening cash monitoring systems, and revising minimum cash policies to enhance liquidity, profitability, and financial resilience.